(untitled) (Ustozlar uchun, 2026)
In the era of globalization, multilingualism has become an essential skill that significantly contributes to individual and societal development. This paper aims to provide a comprehensive analysis of the benefits of knowing more than one language by examining its cognitive, social, cultural, academic, and professional implications. The findings suggest that multilingualism should be actively promoted in modern education systems due to its long-term advantages.